Asthma‐inducing potential of 28 substances in spray cleaning products—Assessed by quantitative structure activity relationship (QSAR) testing and literature review. Issue 1 (11th July 2021) - Hadrup, Niels; Frederiksen, Marie; Wedebye, Eva B.; Nikolov, Nikolai G.; Carøe, Tanja K.; Sørli, Jorid B.; Frydendall, Karen B.; Liguori, Biase; Sejbaek, Camilla S.; Wolkoff, Peder; Flachs, Esben M.; Schlünssen, Vivi; et al.
Abstract: Exposure to spray cleaning products constitutes a potential risk for asthma induction. We set out to review whether substances in such products are potential inducers of asthma. We identified 101 spray cleaning products for professional use. Twenty‐eight of their chemical substances were selected. We based the selection on (a) positive prediction for respiratory sensitisation in humans based on quantitative structure activity relationship (QSAR) in the Danish (Q)SAR Database, (b) positive QSAR prediction for severe skin irritation in rabbits and (c) knowledge on the substances' physico‐chemical characteristics and toxicity. Combining the findings in the literature and QSAR predictions, we could group substances into four classes: (1) some indication in humans for asthma induction: chloramine, benzalkonium chloride; (2) some indication in animals for asthma induction: ethylenediaminetetraacetic acid (EDTA), citric acid; (3) equivocal data: hypochlorite; (4) few or lacking data: nitriloacetic acid, monoethanolamine, 2‐(2‐aminoethoxy)ethanol, 2‐diethylaminoethanol, alkyldimethylamin oxide, 1‐aminopropan‐2‐ol, methylisothiazolinone, benzisothiazolinone and chlormethylisothiazolinone; three specific sulphonates and sulfamic acid, salicylic acid and its analogue sodium benzoate, propane‐1, 2‐diol, glycerol, propylidynetrimethanol, lactic acid, disodium malate, morpholine, bronopol and benzyl alcohol. In conclusion, we identified an asthma induction potential for some of the substances. In addition, we identified major knowledge gaps for most substances. Thus, more data are needed to feed into a strategy of safe‐by‐design, where substances with potential for induction of asthma are avoided in future (spray) cleaning products. Moreover, we suggest that QSAR predictions can serve to prioritise substances that need further testing in various areas of toxicology. Abstract : We reviewed whether substances in spray cleaning products constitute a potential risk for asthma induction. For this, we identified 101 spray cleaning products for professional use and prioritised their ingredient substances by use of quantitative structure activity relationship (QSAR). We provide a review of 28 selected substances: we give conclusions on their asthma induction potential, as well as a discussion on the use of QSAR for prioritisation of substances, and the major knowledge gaps we encountered.